2001
DOI: 10.1042/0264-6021:3570437
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of human plasma α2-Heremans‒Schmid glycoprotein (human fetuin) in vivo

Abstract: A fraction of alpha2-Heremans-Schmid (alpha2-HS) glycoprotein (human fetuin) isolated from plasma was phosphorylated at serine-120 and serine-312 as shown by MS and peptide fragment sequencing after tryptic digestion. Serine-312-containing peptides were phosphorylated to 77% as determined from relative peak heights in the mass spectrum, which together with the phosphorylation of serine-120 implies a molar degree of phosphorylation of at least 1. Approximately 20% of the circulating fetuin plasma pool was phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…Haglund et al demonstrated that 7–20% of the fetuin-A circulating in plasma was phosphorylated, predominantly at Ser312 and to a lesser extent at Ser120 [51]. Recent mass spectrometry based studies of human phosphoproteome have identified four other serine residues that may be partially phosphorylated: Ser134, Ser138, Ser325, Ser334 [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Haglund et al demonstrated that 7–20% of the fetuin-A circulating in plasma was phosphorylated, predominantly at Ser312 and to a lesser extent at Ser120 [51]. Recent mass spectrometry based studies of human phosphoproteome have identified four other serine residues that may be partially phosphorylated: Ser134, Ser138, Ser325, Ser334 [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphofetuin‐A (Ser312) was reduced in 11 of 14 participants but did not reach statistical significance ( p = 0.08), which may be attributed to the small sample size. Human fetuin‐A is phosphorylated on Ser120 and Ser312 with most of the phosphorylation on Ser312 35. The phosphorylation status has been shown to be critical for the inhibitory action of fetuin‐A in rats and implicated in humans 5, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
“…Fet‐A exists in circulation in both phosphorylated (~20%) and dephosphorylated (~80%) forms . Of the two phosphorylation sites on Fet‐A, serine312 (Ser312) was shown to be the dominant phosphorylation site, displaying ~77% phosphorylation compared with serine120 . We and others have shown that phosphorylation status is critical for its inhibitory effects on insulin‐stimulated insulin receptor autophosphorylation, insulin receptor tyrosine kinase activity, glucose uptake, and glycogen synthesis .…”
Section: Introductionmentioning
confidence: 99%